1990
DOI: 10.1111/j.1476-5381.1990.tb14705.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuropeptide Y on cardiac output, its distribution, regional blood flow and organ vascular resistances in the pithed rat

Abstract: 1 The effects of neuropeptide Y on cardiac output, its distribution and organ vascular resistances were determined with tracer microspheres in pithed rats. 2 Neuropeptide Y increased blood pressure by increasing both cardiac output and total peripheral resistance. The increase in cardiac output was due to an increase in stroke volume as heart rate was not changed. Increased vascular resistance in the splenic, renal, testicular, epididimidal, skeletal muscle, large intestinal and mesenteric vascular beds contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

1991
1991
1997
1997

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…The results of the present study indicate that NPY is a potent vasoconstrictor in the gastric mucosal microcirculation, as assessed by laser Doppler flowmetry. This finding extends previous studies demonstrating vasoconstrictor actions of NPY on splenic, renal, testicular, skeletal muscle, and large or small intestinal vascular beds Hellstrom, 1987;Westfall et al, 1987;MacLean & Hiley, 1990). The present study also demonstrates that local intra-arterial infusion of noradrenaline will reduce gastric mucosal blood flow in the rat.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study indicate that NPY is a potent vasoconstrictor in the gastric mucosal microcirculation, as assessed by laser Doppler flowmetry. This finding extends previous studies demonstrating vasoconstrictor actions of NPY on splenic, renal, testicular, skeletal muscle, and large or small intestinal vascular beds Hellstrom, 1987;Westfall et al, 1987;MacLean & Hiley, 1990). The present study also demonstrates that local intra-arterial infusion of noradrenaline will reduce gastric mucosal blood flow in the rat.…”
Section: Discussionsupporting
confidence: 92%
“…This has been confirmed in many species in vivo. In the pithed rat the cardiovascular effects of intravenous administration of neuropeptide Y has been shown to be peripheral and thus not mediated by a central reflex (MacLean & Hiley 1990). It has been demonstrated that low frequency stimulation of motor neurones decreased microvessel diameters in rabbit skeletal muscle, an effect sensitive to phentolamine, thus involving a-adrenoceptors receptors.…”
Section: Na-neuropeptide Ymentioning
confidence: 99%
“…NPY induces vasoconstriction in the vascular beds of the spleen and large and small intestine (Lundberg et al, 1982;Hellstrom, 1987;Westfall et al, 1987;MacLean & Hiley, 1990;Sheikh, 1991). In addition, local intra-arterial infusion of NPY has been shown to reduce rat gastric mucosal blood flow, as determined by laser Doppler flowmetry (MacLean & Hiley, 1990).…”
Section: Microvascular Ischaemia and Injurymentioning
confidence: 99%
“…In addition, local intra-arterial infusion of NPY has been shown to reduce rat gastric mucosal blood flow, as determined by laser Doppler flowmetry (MacLean & Hiley, 1990). The inability of the a1-adrenoceptor antagonist, prazosin, to overcome the effect of NPY in the gastric circulation is consistent with other findings in the mesenteric circulation of the rat (Westfall et al, 1987), indicating that NPY, like noradrenaline, affects the gastric microcirculation by actions directly on gastric vascular smooth muscle, but through activation of a distinct receptor type.…”
Section: Microvascular Ischaemia and Injurymentioning
confidence: 99%